Analisis Pemetaan Industri Kreatif Sektor Kerajinan Sebagai Strategi Pengembangan Ekonomi Kabupaten Pemalang - Febriyanti Nur Izzati; Hetika Hetika; Fitri Amaliyah (JURNAL RISET TERAPAN AKUNTANSI, 2020)
TheCreative economies have been developed in various countries and show significant positive results, including employment and additional regional income. The development of the handicraft industry is part of the industrialization process that is broad-minded and has an important contribution to the development of the regional economy. Methods of collecting the data used in this research were interviews, observation, and literature study. Data analysis methods used in this research were SWOT (strengths, weaknesses, opportunities, threats) analysis and SWOT matrix. The results of the study of mapping the creative industry of the craft sector conducted in Pemalang Regency based on the SWOT Analysis when viewed from the calculation of internal strategy factors the total strengths and weaknesses of 2.973 while the external strategy factors total opportunities and threats of 2.78. This shows that the creative industry of the handicraft sector in Pemalang Regency has good strengths and opportunities from the weaknesses and threats that occur. So that if they are able to make the best use of the opportunities, they can increase the regional economic income of Pemalang Regency. Based on the SWOT matrix, a suitable strategy is used in the creative industries of the craft sector, namely the SO strategy, which is to use strength in exploiting opportunities.